Mango Fruit Extracts Differentially Affect Proliferation and Intracellular Calcium Signalling in MCF-7 Human Breast Cancer Cells - Meng-Wong Taing; Jean-Thomas Pierson; Paul N. Shaw; Ralf G. Dietzgen; Sarah J. Roberts-Thomson; Michael J. Gidley; Gregory R. Monteith (Journal of Chemistry)
The assessment of human cancer cell proliferation is a common approach in identifying plant extracts that have potential bioactive effects. In this study, we tested the hypothesis that methanolic extracts of peel and flesh from three archetypal mango cultivars, Irwin (IW), Nam Doc Mai (NDM), and Kensington Pride (KP), differentially affect proliferation, extracellular signal-regulated kinase (ERK) activity, and intracellular calcium ([Ca2+]I) signalling in MCF-7 human breast cancer cells. Mango flesh extracts from all three cultivars did not inhibit cell growth, and of the peel extracts only NDM reduced MCF-7 cell proliferation. Mango cultivar peel and flesh extracts did not significantly change ERK phosphorylation compared to controls; however, some reduced relative maximal peak [Ca2+]I after adenosine triphosphate stimulation, with NDM peel extract having the greatest effect among the treatments. Our results identify mango interfruit and intrafruit (peel and flesh) extract variability in antiproliferative effects and [Ca2+]I signalling in MCF-7 breast cancer cells and highlight that parts of the fruit (such as peel and flesh) and cultivar differences are important factors to consider when assessing potential chemopreventive bioactive compounds in plants extracts.